Effect of the interaction between fungicide application time and rainfall simulation interval on Asian Soybean Rust control effectiveness - Stefanello, Marlon Tagliapietra (2016)
Environmental factors affect the performance of fungicides in soybean (Glycine max (L.) Merr.). They also influence the residual activity of the products applied to the leaves. The objective of this study was to assess the control effectiveness of the interaction between fungicide application and rainfall simulation on Asian Soybean Rust (ASR). Two experiments were conducted, one in the greenhouse, in a completely randomized design, and the other in the field, in a randomized block design. Both the experiments had the same factorial arrangement of 6x5, with four replications. Factor A: Five fungicide applications time at 0400 h, 0900 h, 1400 h, 1800 h, 2300 h and, a control with no application; Factor B: four intervals of time between the application of fungicide and rainfall simulation at 0, 30, 60 and 120 min for the experiment in the greenhouse and at 2, 30, 60, 120 min for the experiment in the field. A control was included for both the experiments with no rainfall. The number of days to the appearance of the first pustules was determined, along with severity of ASR, relative chlorophyll index and productivity. It was found that the ASR control effectiveness of fungicide applications in soybean plants in sunlight was less efficient with rainfall simulation. The rainfall simulation had greater negative effect on disease control effectiveness in applications conducted at night under dew conditions. The application conducted at 0900 h showed the greatest disease control effectiveness in both greenhouse and in the field conditions. The 1400 h application showed decreased fungicide control residual and ASR control effectiveness, possibly due to a combination of the low relative humidity and high temperature. Rainfall simulation carried out at 120 min after application still had the ability to affect the ASR control effectiveness.